SIMAPA System Testing Using Alpha and Beta Tests - Puspaningrum , Eva Yulia; Yudha K., Dhian Satria; Utami, Hapsari Wiji; Via, Yisti Vita; Mandyartha, Eka Prakarsa; Maulana, Hendra (Nusantara Science and Technology Proceedings, 2023)
The SIMAPA system is a system for monitoring children's activities and development which is implemented at KB-TK Agripina Surabaya. The SIMAPA system has been designed using system development, namely SDLC (System Development Life Cycle). The system can be declared valid and by what is expected if testing has been carried out. An application can be tested using collaborative alpha and beta testing using the black box method. Alpha testing is carried out to see whether all systems can run well and is carried out by the system manufacturer. Meanwhile, in beta testing, the party who will assess the system is the user or people who are not involved in creating the system. This testing is carried out by distributing questionnaires to several users to assess the application that has been built. The questionnaire contains questions about the system being built so that it can be concluded whether the application is by the objectives. The results of the Beta test with 6 questions about the system obtained good results with an average score of 92%. so that the system built is by what is expected.